PELATIHAN DESIGN THINKING PADA UMKM BINAAN KAMPUNG DIGITAL SENTRA KREASI - Didit Widiatmoko Soewardikoen; Andreas Rio Adriyanto; Aria Ar Razi (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Micro, Small and Medium Enterprises (MSMEs) are the mainstay for the Indonesian economy. The pandemic, which has lasted two years and is still ongoing, has an impact on MSME entrepreneurs. The problem that is often encountered is that entrepreneurs are not ready to face sudden changes in the situation. This problem occurs in MSME entrepreneurs in Pameungpeuk District and its surroundings who are members of the MSMEs assisted by the Sentra Kreasi Digital Village Community. Innovation and development of products or services that can respond to these changes is needed. Community service by holding appropriate training to answer this problem, namely design thinking training which is expected to be able to make entrepreneurs remap and develop their products through innovation. The results of this training are to add insight and improve the skills of MSME entrepreneurs in developing products or services in dealing with disruption situations.